Application of Omnichannel Strategy and Content Personalization to Customer Loyalty in the Fashion Retail Industry in Makassar - Sudirjo, Frans; Saununu, Siska Jeanete; Harahapi, Taufik (West Science Interdisciplinary Studies, 2024)
This study explores the impact of an omnichannel strategy and content personalization on customer loyalty in the fashion retail industry in Makassar. Using a quantitative approach, data were collected from 60 respondents through a structured questionnaire and analyzed using SPSS version 26. The study measured the relationships between omnichannel strategy, content personalization, and customer loyalty using a Likert scale (1-5). Results from Pearson correlation and multiple regression analyses indicated significant positive relationships between omnichannel strategy and customer loyalty (r = 0.72, p < 0.01) as well as content personalization and customer loyalty (r = 0.68, p < 0.01). The regression model explained 62% of the variance in customer loyalty, confirming the combined influence of these strategies on fostering customer retention. The findings suggest that fashion retailers in Makassar can enhance customer loyalty by offering seamless omnichannel experiences and personalized content that meets individual preferences.